LINC00667 Sponges miR-4319 to Promote the Development of Nasopharyngeal Carcinoma by Increasing FOXQ1 Expression - Liao, Bing; Yi, Yun; Zeng, Lei; Wang, Zhi; Zhu, Xinhua; Liu, Jianguo; Xie, Bingbin; Liu, Yuehui (Frontiers in Oncology, 2021)
Accumulating evidence has indicated that lncRNAs regulate various biologicaland pathological processes in diverse malignant tumors. The roles of LINC00667 in cancer development have been explored in glioma, hepatocellular carcinoma and non-small cell lung cancer, but not in nasopharyngeal carcinoma (NPC). In the present study, we characterize the role and molecular mechanism of LINC00667 in NPC progression. It was found that LINC00667 was overexpressed in NPC cells compared to normal cells. Silencing LINC00667 suppressed the proliferation, migration, invasion and EMT in NPC cells. In addition, bioinformatics analysis revealed that LINC00667 acted as a ceRNA to absorb miR-4319. Further investigations illustrated that miR-4319 had low expression in NPC cells and functioned as a tumor suppressor in the progression of NPC. Mechanistic study identified FOXQ1 as a functional target of miR-4319. The effect of LINC00667 in NPC development was mediated by the miR-4319/FOXQ1 axis. Analysis on tumor xenograft mouse model demonstrated that knockdown of LINC00667 repressed NPC tumor growth in vivo and confirmed the in vitro results. This study suggested that LINC00667 promoted the malignant phenotypes of NPC cells by competitively binding to miR-4319 to up-regulate FOXQ1 expression. Our results unraveled that LINC00667 could be a diagnostic and therapeutic target for NPC patients.